An integrated approach for the planning of dredging operations in estuaries. (1st August 2017) - Álvarez, M.; Carballo, R.; Ramos, V.; Iglesias, G.
Abstract: Ports are often located in naturally sheltered areas such as estuaries. The strong tidal currents that occur in many of these areas drive a dynamic morphodynamic regime, with the result that the approach channels to these ports are gradually infilled. Periodic dredging is therefore necessary to maintain the operativity of the port. A case in point is Ribadeo (NW Spain), an important port for the economy of the area. In this work, the sediment transport patterns of the estuary (Ria de Ribadeo) are investigated through high-resolution numerical modelling and field measurements covering a 4-year period. On this basis, a decision-aid tool is developed that enables to predict the time evolution of the approach channel and thus contributes to the planning of dredging operations and, more generally, the maintenance of adequate operativity levels in a cost-effective way. Highlights: An integrated approach is developed for designing dredging operation plans. High resolution hydromorphodynamic modelling is conducted. The approach allows the definition of the appropriate time point to conduct dredging. The procedure could be implemented in any coastal region of interest.